2016
DOI: 10.1038/nature20564
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing human antibodies prevent Zika virus replication and fetal disease in mice

Abstract: Zika virus (ZIKV) is an emerging mosquito-transmitted flavivirus that can cause severe disease, including congenital birth defects during pregnancy1. To develop candidate therapeutic agents against ZIKV, we isolated a panel of human monoclonal antibodies from subjects that were previously infected with ZIKV. We show that a subset of antibodies recognize diverse epitopes on the envelope (E) protein and exhibit potent neutralizing activity. One of the most inhibitory antibodies, ZIKV-117, broadly neutralized inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
461
2
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 362 publications
(484 citation statements)
references
References 33 publications
15
461
2
6
Order By: Relevance
“…Recent studies show that maternal antibodies can transfer into the developing peripheral and central nervous system during gestation [11,18]. These findings coupled with reports that maternal antibodies are effective against congenital Zika [19] and cytomegalovirus [20] infections suggest a broader applicability of maternal immunizations to other TORCH pathogens.…”
mentioning
confidence: 62%
“…Recent studies show that maternal antibodies can transfer into the developing peripheral and central nervous system during gestation [11,18]. These findings coupled with reports that maternal antibodies are effective against congenital Zika [19] and cytomegalovirus [20] infections suggest a broader applicability of maternal immunizations to other TORCH pathogens.…”
mentioning
confidence: 62%
“…However, the sudden ZIKV outbreak in South America alerted health authorities and the public to develop a vaccine. Preclinical studies have demonstrated a protective role of CD8 T cells and antibodies against ZIKV infection, the latter being sufficient for complete protection [67][68][69][70]. However, cocirculation of DENV, WNV and ZIKV has been reported in several countries and previous studies suggested an immunological cross-reactivity between viruses, which may drive immune-mediated enhancement [71][72][73].…”
Section: Zika Virusmentioning
confidence: 96%
“…Zika virus enfeksiyonlarına için spesifik tedaviler henüz deneme aşamasındadır. Yakın zamanda yayımlanan bir makalede, araştırmacılar insan monoklonal antikorların (ZIKV-117) Zika virus kökenlerini hücre kültürü ve fare modelinde (gebelik süreci de dâhil olmak üzere) nötralize ettiğini gösterdiler (46) . Konvelesan serum veya plazmanın enfeksiyona karşı koruyucu özellik-leri de araştırılmış ve umut verici sonuçlar elde edilmiştir (13) .…”
Section: Tedaviunclassified